Biosensors in Perspective in the New Normal Era: Ultrasonic as an Innovative Early Detection of Fruit Flies Infestation on Sweet Arum Mango - Wiwin Windriyanti; Mira Eka Nursandi (Nusantara Science and Technology Proceedings, 2021)
The attack of fruit fly larvae in the flesh of the sweet arum mango can be detected without opening the fruit by a detection method using ultrasonic waves. The characteristics of ultrasonic waves used are attenuation coefficient, speed and zero moment power (Mo). In whole mango, the attenuation coefficient is 36.45 Np/M with ultrasonic wave speed 518.19 m/sec and zero moment power (Mo) 4.58. In its application, the estimation of the damage of the sweet arum mango with ultrasonic waves at the limit of attenuation coefficient of 34.76 Np/M, zero moment power (Mo) 5.60. The estimated attenuation coefficient of more than 34.76 Np/M mango fruit was declared intact, while the attenuation coefficient 34.76 Np/M was thought to have been attacked by fruit fly larvae. At the value of zero moment power (Mo) > 5.6 mangoes are declared intact, but if the Mo is 5.60, it is declared to have been attacked by fruit fly larvae in it. The use of the ultrasonic sensor HC-SR04 is effective in detecting the attack of fruit fly larvae (Bactrocera dorsalis) in the flesh of the sweet arum mango at a distance of 6 cm with a warning sound indicator on the LCD. If the output voltage value on the LCD shows > 30 mV, the buzzer will sound which indicates that the fruit inside has softened due to being attacked by fruit fly larvae or due to impact, on the contrary if the output voltage value is 30 mV and the buzzel does not sound, it indicates the mango is still healthy and intact.